Naik ke Sorga, Duduk di Sebelah Kanan Allah Bapa yang Mahakuasa: Suatu Tinjauan Teologis-Dogmatis terhadap Rumusan Pengakuan Iman Rasuli Alinea 2 - Sisco Turnip, Ricardo; Humala Pakpahan, Jordan; Fasius Banjarnahor, Irsanto Boni; Sri Sinaga, Dewi (CV. Creative Tugu Pena, 2021)
The purpose of this research is to understand the Biblical and Theological basis for the meaning of the sentence